2018
DOI: 10.1021/acs.jpcc.8b08613
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of the Electronic Structure and Defect Formation Enhances Photocatalytic Efficiency of Gallium Tin Oxide Nanocrystals

Abstract: The design of photocatalysts with enhanced efficiency is pivotal to sustainable environmental remediation and renewable energy technologies. Simultaneous optimization of different factors affecting the performance of a photocatalyst, including the density of active surface sites, charge carrier separation, and valence and conduction band redox potentials, remains challenging. Here, we report the synthesis of ternary gallium tin oxide (GTO) nanocrystals (NCs) with variable composition and investigate the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The molten salts help achieve phase pure products with homogeneous powder characteristics and controlled size/shape at relatively low temperature compared to the SSR . It offers advantages including being simple to operate, exhibiting rapid product formation, facilitating large scale production, being cost-effective, having low product defect density, a ligand free surface, and reproducibility, and being environment friendly. ,,, Nanomaterials synthesized by the MSS method are generally highly homogeneous and phase pure, having controlled size and morphology, and most of the time, they have the formed particle size being in the range of tens of nanometers …”
Section: Introductionmentioning
confidence: 99%
“…The molten salts help achieve phase pure products with homogeneous powder characteristics and controlled size/shape at relatively low temperature compared to the SSR . It offers advantages including being simple to operate, exhibiting rapid product formation, facilitating large scale production, being cost-effective, having low product defect density, a ligand free surface, and reproducibility, and being environment friendly. ,,, Nanomaterials synthesized by the MSS method are generally highly homogeneous and phase pure, having controlled size and morphology, and most of the time, they have the formed particle size being in the range of tens of nanometers …”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that heterogeneous photocatalysis was discovered almost half a century ago, numerous studies focusing on the fundamental physical chemistry of this process are still being published every year. Some of the most recent studies can be found in refs . Presently, the primary focus is on the synthesis and characterization of photocatalysts that are tailored for specific applications, e.g., oxidative degradation of pollutants, reductive degradation of pollutants, or hydrogen production. A general aim has been to produce photocatalysts that are activated by visible light, either to drive reactions with less energy input or to more closely match the solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most recent studies can be found in refs . Presently, the primary focus is on the synthesis and characterization of photocatalysts that are tailored for specific applications, e.g., oxidative degradation of pollutants, reductive degradation of pollutants, or hydrogen production. A general aim has been to produce photocatalysts that are activated by visible light, either to drive reactions with less energy input or to more closely match the solar spectrum. The catalytic efficiency of a photocatalyst can be increased by prolonging the lifetime of the hole–electron pair generated upon illumination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Examples include the generation of localized surface plasmon resonance in TCO nanocrystals (NCs), [15][16][17] room-temperature ferromagnetism in diluted D r a f t magnetic semiconductor oxide (DMSO) NCs, 6,[18][19][20][21][22] size-and composition-tunable light emission, [23][24][25] and selective and efficient photocatalysts. [26][27][28][29][30] Among transparent metal oxides, Ga 2 O 3 is considered the widest band gap semiconductor. Although the first systematic studies of Ga 2 O 3 were reported back in 1950's and 1960's, 7,31,32 it has been much less investigated over the ensuing decades compared to other oxides, such as ZnO, TiO 2 , or SnO 2 .…”
Section: Introductionmentioning
confidence: 99%